Educational Studies Examining Knowledge of Substance Use Disorders and Career Aspirations Among Medical Trainees in an Inner-City Hospital. Issue 1 (January 2022) - Gooding, Luke; Hamilton, Michee-Ana; Dong, Huiru; Wood, Evan; Cullen, Walter; Fairbairn, Nadia; Nolan, Seonaid; Klimas, Jan
Abstract : Objectives: Gaps in addiction medicine training are a reason for poor substance use care in North America. Hospital addiction medicine consult services (AMCS) provide critical medical services, including screening and treatment of substance use disorders. Although these programs often feature an educational component for medical learners, the impact of AMCS teaching on objective knowledge and career aspirations in addiction medicine has not been well described. Methods: The authors report findings from two sequential studies conducted at a large academic hospital in Vancouver, Canada. The first study assessed the impact of an AMCS clinical rotation on medical trainee addiction medicine objective knowledge using an online survey of 6 true/false questions before and after the rotation. The second study examined the impact of an AMCS rotation on career aspirations using 4 seven-point Likert-type questions. One-sample t tests on mean differences (MD) with Benjamini-Hochberg adjustment for multiple comparisons were employed for statistical analyses. Results: Between May 2017 and June 2018, knowledge scores were significantly higher postrotation (MD = 4.78, standard deviation [SD] = 19.5, P  = 0.034) among 115 medical trainees. Between July 2018 and July 2019, aspirations to practice addiction medicine were significantly more favorable postrotation (MD = 3.48, SD = 3.15, P  < 0.001) among 101 medical trainees. Conclusions: AMCS rotations appear to improve addiction medicine knowledge and aspirations to practice addiction medicine among medical trainees. Larger-scale evaluations and outcomes research on integrating substance use disorders teaching in these settings will help move the discipline forward. Abstract : Supplemental Digital Content is available in the text